PENGGUNAAN KALIMAT PADA PAPAN REKLAME DAN SPANDUK (DITINJAU DARI SEGI MORFOFONEMIK) - Utami, Sri (Jurnal Likhitaprajna, 2018)
ABSTRACTÂ Language as a communication tool that develops according to the situation and development of society, always chooses the right way to communicate effectively and efficiently. The use of language that is always developing is what needs to be investigated for its development, especially in morphological writing in order to find theories about language writing. Therefore researchers want to prove that a person's knowledge or knowledge when doing lessons or learning is not just sitting in a classroom or a room by paying attention to the teaching staff, but being anywhere when we are active. This is evident that not only in class can receive knowledge even in the streets can also get knowledge. The data sources of this study are billboards and banners. The research technique is done by observing the use of sentences on billboards and banners. After observing, the sentence forms that contain morphophonemic (morphological) elements were observed. Data analysis was carried out by recording a number of sentences containing morphophonemic forming elements, which were then referred to relevant theories, so that sentences containing morphophonemic elements were found and then given the correct analysis results. The results showed that morphophonemic analysis of the use of sentences on banners and billboards had morphological forming elements referred to in morphophonemic forming elements in the process of phoneme change and phoneme dating.Keywords: morphophonemic, sentences on banners and billboards